PERSPEKTIF EKONOMI DAN BISNIS ISLAM MENGENAI PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA ALFAMART CIBATOK KECAMATAN ‎CIBUNGBULANG, KABUPATEN BOGOR - Handayani, Fitri; Thantawi, Tubagus Rifqy; Mubarok, Muhammad Kharis (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The aim of this research is to analyze and explain whether the independent variables (Price and Service Quality) have a positive and significant effect on the dependent variable (Consumer Satisfaction). The method used in this research is quantitative and associative in nature. The subjects of this research are customers who shop at Alfamart Cibatok, Cibungbulang District, Bogor Regency. The data analysis method used is multiple linear analysis. The results of this research show that (1) the significance value is 0.002 which is smaller (<) than 0.05. This means that there is a significant influence between price and consumer satisfaction. (2) The significance value is 0.000 which is smaller (<) than 0.05. This means that there is a significant influence between Service Quality and Consumer Satisfaction. (3) Simultaneously the F count is 987.521 with a sinificance result of 0.000 and F table = F (k; n-k) = F = (2;97) = 3.09 which results indicate that the F count of 987.521 is greater (>) of 3.09 and sig value. of 0.00 is smaller (<) than 0.05. This means that price and service quality simultaneously have a significant influence on consumer satisfaction. From an Islamic economic and business perspective, the prices set by Alfamart Sat Raya Cibatok, Cibungbulang District, Bogor Regency are in accordance with Islamic economic and business concepts, namely using the principles of justice, mutual consent from both parties, no element of coercion, and no who is harmed by one of the parties (zholim). In terms of service quality, Alfamart Sat Raya Cibatok, Cibungbulang District, Bogor Regency has provided excellent service in running its business and is in line with Islamic economic and business principles. One of them is providing empathy to consumers by greeting them, giving a smile and giving individual attention wholeheartedly. Furthermore, to find out how much the independent variable explains the related variable, it can be shown in the correlation coefficient value of 0.952 which shows that 0.952 or 95.2% of consumer satisfaction can be influenced by price and service quality and the remaining 4.8% of consumer satisfaction is influenced by variables. other.